Overview on natural dyes and their IR-spectra – Part II: Indigo containing plant dyes - Boris Mahltig (Communications in Development and Assembling of Textile Products, 2024)
This review paper is part of a paper series reporting on natural dyestuffs and their infrared spectra (IR spectra). The current part II is related to the dye indigo (vat blue 1). Indigo is probably the most used and the most important dye. It is related to the typical clothing product – the blue jeans. In current study, the IR spectra of natural indigos from different origin are determined and compared to the IR spectrum of synthetic indigo. Further discussed materials are a powder of indigo leaves, a pigment named indigo green, the dye indigotine blue and the natural indigoid dye tyrian purple. The recorded spectra are discussed with respect to the chemical structure of the dye and with view to the presence of possible byproducts. It is possible to estimate the origin of natural indigo by infrared spectroscopic measurements of a certain plant source. The presented overview can be used as helpful tool for persons working in the field of dyeing or quality control to support and help them to identify products by IR-spectroscopic methods.